Gastric alarmin release: A warning signal in the development of gastric mucosal diseases - Wu, Enqin; Zhu, Jiaxing; Ma, Zhiyuan; Tuo, Biguang; Terai, Shuji; Mizuno, Kenichi; Li, Taolang; Liu, Xuemei (Frontiers in Immunology, 2022)
Alarmins exist outside cells and are early warning signals to the immune system; as such, alarmin receptors are widely distributed on various immune cells. Alarmins, proinflammatory molecular patterns associated with tissue damage, are usually released into the extracellular space, where they induce immune responses and participate in the damage and repair processes of mucosal diseases.In the stomach, gastric alarmin release has been shown to be involved in gastric mucosal inflammation, antibacterial defense, adaptive immunity, and wound healing; moreover, this release causes damage and results in the development of gastric mucosal diseases, including various types of gastritis, ulcers, and gastric cancer. Therefore, it is necessary to understand the role of alarmins in gastric mucosal diseases. This review focuses on the contribution of alarmins, including IL33, HMGB1, defensins and cathelicidins, to the gastric mucosal barrier and their role in gastric mucosal diseases. Here, we offer a new perspective on the prevention and treatment of gastric mucosal diseases.